The Sun Festival and Variations in Traditional Kayambi Women’s Attire - Echeverría Cachipuendo , Galo Oswaldo; Cruz Góngora , Fabio Elton; Flores Ruiz , Jorge Armando; Imbago Arias, Oswaldo Aníbal (SATHIRI, 2025)
The scientific article addresses variations in the traditional dress of the kayambi people, an indigenous group located in the Andean region of Ecuador, with the objective of documenting and analyzing changes in their textile practices over time. The research is based on a combination of bibliographic compilation, field studies in different parishes of Cayambe and an exhaustive ethnographic registry. First, a literature review was conducted that included previous historical and anthropological studies on kayambi dress, providing a fundamental context for understanding the evolution of their traditional costumes. Next, an extensive field study was conducted in several parishes of Cayambe, where researchers observed and documented current practices in relation to traditional dress. The ethnographic analysis revealed notable differences between ancient and current dress. Traditional garments, once made primarily of alpaca wool fabrics and elaborate trimmings, have undergone significant changes. The influence of globalization and modernization has led to an incorporation of synthetic materials and a more simplified design. In addition, the use of traditional dress has decreased in everyday contexts and has been limited mostly to ceremonial events. The study concludes that although traditional kayambi dress has evolved due to socioeconomic and cultural factors, it remains a key element of cultural identity and resilience. The research provides a comprehensive view of how indigenous communities adapt their traditions in a changing world.